Effect of Organic and Inorganic Fertilizers on Growth, Yield and Quality Tomato (Lycopersicon esculentum Mill.) - Nirmala Sharma; Kailash Agrawal; Ishwar Patil (Revista Electronica de Veterinaria, 2024)
This two-year field study (2021–22 and 2022–23), looked at how organic and inorganic fertilizers affect tomato plants. The goal was to see how these fertilizers impact growth, yield, quality, and economic feasibility. Sixteen combinations of fertilizers were tested, including inorganic fertilizers at different rates (0%, 50%, 75%, and 100% recommended dose) and organic fertilizers like Panchgavya, Jeevamrutha, and a plant growth-promoting spray (PGPOS). Higher levels of inorganic fertilizers improved plant growth, while PGPOS gave the best results among the organic fertilizers. Both fertilizers increased fruit weight and yield. Quality measures like vitamin C, chlorophyll, and lycopene also improved with more fertilizer. The highest economic return came from the 100% RDF with PGPOS. Overall, proper fertilizer use can significantly improve tomato production and quality. However, no significant interaction was observed between the types of inorganic and organic fertilizers. From an economic perspective, the highest benefit-cost ratio (B) was achieved with the 100% RDF and PGPOS treatments, proving their economic feasibility. This study emphasizes the advantages of proper fertilizer application in improving tomato production and quality.